From Iran and Saudi Arabia to Indonesia: The Translation of Shi‘ite and Wahhabi Literature in Contemporary Indonesia - Syahnan, Mhd.; Mukhsin, Abd.; Ja'far, Ja'far (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2023)
This study examines the translation of Shi‘ite and Wahhabi literature in Indonesia. This is a literature study. The primary data was obtained by examining the record of translated and published titles in Indonesian. This study refers to the theory of Mehdi Nakosteen, R.G.A. Dolby, and Abdul Munip regarding the transmission of knowledge through translation activities, their phases, and motives. This study found that these books from Iran and Saudi Arabia, covering various Islamic knowledge, are published and distributed in Indonesia by affiliated and unaffiliated publishers in order to introduce their ideas and doctrines to the wider Muslim community in Indonesia, using the Indonesian language as the medium of transmission. This transmission of knowledge through translation takes place through the awareness, interest, and adoption phases, and has religious, educational, economic, ideological, and stimulative-provocative motivations.